Final Year Project Management System For Faculty Of Computing - Nurayuni, Nordin Sin (2023)
With the development of technologies nowadays, the government and non-government institutes have started applying the project management system in their operation in order to make it easier for implementation and handling. However, the implementation of a project management system for the final year project in the Faculty of Computing at the Universiti Malaysia Pahang is unsystematic and utilises many applications simultaneously. At the same time, there is a certain process of a project management system that is still not computerized yet. Hence, the development of the Final Year Project Management System for Faculty of Computing will improve the process and management of the final year project in becoming more systematic, organized, convenient, and computerized. In fact, it can fulfil the goal of a ‘Green Campus’ since the Final Year Project Management System for Faculty of Computing will contribute to the paperless activity. The Final Year Project Management System for Faculty of Computing will be developed using the Agile methodology for the easily development and upgrading. In the evaluation phases, the Final Year Project Management System for Faculty of Computing will be tested by the final year students, lecturer, and coordinator of PSM/PTA in the Faculty of Computing in order to prove that the system has achieved the users’ requirements. In short, the Final Year Project Management System for Faculty of Computing will achieve the objectives and goals of the system. In fact, the system also manages to fulfil the user's and admin's satisfaction through its functionality.